Variation of glyphosate spray volume in the drying of ground cover plants with an unmanned aerial vehicle - Carneiro, Rodrigo Pereira; Garcia, Luiz Cláudio; Dalazen, Giliardi; Gomes, Jaime Alberti; Raetano, Carlos Gilberto [UNESP]; Boller, Walter (Elsevier, 2024)
The presence of straw on the soil is crucial for enhancing its physical, chemical, and biological conditions in no-tillage cropping systems, while contributing to weed control. This study aimed to determine the optimal spray volume for desiccating ground cover plants using glyphosate applied by an unmanned aerial vehicle (UAV). Treatments included an untreated control and glyphosate spraying at 5, 10, 15, 20, and 25 L ha−1 spray solution. The study was conducted in three fields in the State of Paraná, Brazil. Spraying variables were assessed using water-sensitive paper and the e-Sprinkle software, and included, covered area (%), recovered spray volume (L ha−1), droplet impact density, coefficient of variation for droplet diameter (CV%), and relative amplitude (SPAN). Herbicidal efficacy and dry biomass of cover plants were also evaluated. Increasing spray volume improved covered area, recovered volume, droplet impact density, and droplet diameter-spectrum variation but had no effect on droplet spectrum homogeneity, control of black oat (Avena strigosa), turnip (Raphanus sativus), or buckwheat (Fagopyrum esculentum). Spray volumes ranging from 5.0 to 25 L ha−1, applied with a UAV, provided satisfactory desiccation percentages of ground cover plants irrespective of species or location. Thus, for desiccating ground cover plants with glyphosate applied by UAV, a volume as low as 5.0 L ha−1 is effective.
Keywords: Application technology; Drone; Herbicide; Spray quality